PERBEDAAN QIRA’AT AL-QUR'AN DALAM AT-TAQDIM WA AT-TA'KHIR DAN IMPLIKASI TAFSIRANNYA - Ukhti Luthfiyyah; Abdur Rokhim Hasan; Khairul Azmi (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2026)
This study aims to identify the forms of al-taqdīm wa al-ta’khīr in Qur’anic qira’at and to analyze their implications for Qur’anic exegesis. This research employs a qualitative method based on library research, referring to primary sources such as classical works on qira’at and Qur’anic exegesis, as well as secondary sources including contemporary books and academic journals. The approaches used include a linguistic approach to analyze language structures, a qira’at approach to trace recitational variations, and a thematic exegesis approach to understand the semantic implications of these differences. The findings indicate that al-taqdīm wa al-ta’khīr in qira’at is not merely a textual variation, but carries significant rhetorical and semantic functions. Variations in word order provide emphasis on particular meanings, highlight conceptual priorities, and broaden the interpretive scope of Qur’anic verses. These findings affirm that variations in qira’at, particularly in the form of al-taqdīm wa al-ta’khīr, contribute to enriching the exegetical tradition without generating contradiction. Thus, qira’at can be understood as an interpretive instrument that demonstrates the flexibility of the Qur’anic language in responding to various contexts and deepening the understanding of its message.